Computational optimisation of the thermal fusion bonding process in porous fibrous media for improved product capacity and energy efficiency - Murat Peksen; Memis Acar; Weeratunge Malalasekera (2012)
A comprehensive parametric study to aid in optimising the thermal fusion bonding process in porous fibrous media is introduced. A systematic approach considering computational fluid dynamics, design of experiments and statistical process control is attempted. The effects of several operating and design parameters on the thermal bonding performance have been systematically investigated. An experimentally validated two-dimensional computational fluid dynamics model based on the theory of porous media has been used for the study. The air velocity and the conveyer belt porosity are determined to be showing the greatest optimisation potential for higher production rates. The optimum thermal fusion bonding process for the highest production rates and energy efficiency has been determined considering the thermal bonding time and percentage increase in total web energy absorption. Another outcome is the improved product quality associated with the improved temperature gradients within the fibrous web. © IMechE 2012.